DIAGNOSIS JANGKITAN (INFEKSI) VIRUS DENGUE DENGAN UJI CEPAT (RAPID TEST) IgA ANTI-DENGUE - Sri Kartika Sari; Aryati Aryati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Dengue IgM, IgG Capture ELISAs and NS1 Ag ELISA become the most widely used serological methods for dengue diagnosis untilnow. Previous studies reported a possible use of IgA antibodies for dengue virus as a new serologic marker to make dengue infectionactive. In the present study, the performance of IgA anti-dengue rapid test as a new marker of dengue infection was assessed. In thisstudy, the sera were obtained from 30 dengue virus infection patients and 30 non dengue virus infection patients. Thirty dengue pairedsera were collected twice, at the time of hospital admission (acute) and at discharge (convalescent). All sera samples were characterizedusing dengue reference ELISAs (NS1 Ag, Dengue IgM and IgG capture ELISAs). The results of IgA anti-dengue rapid test were comparedwith the corresponding dengue reference tests. The sensitivity and specificity of IgA anti-dengue rapid test respectively were 78.3% (95%CI: 65.5–87.5%), and 73.3% (95% CI: 55,6–85,8%). Meanwhile, from acute sera, sensitivity of IgA anti-dengue rapid test was 83.3%(95% CI: 64.5–93.7), higher than IgM (73.3%, 95% CI: 53.8–87.0), IgG (66.7%, 95% CI: 47.1–82.1) and NS1 Ag ELISAs (60%,95% CI: 40.7–76.8). Positive IgA anti-dengue rapid test results in acute sera was higher in the secondary (91%) than primary infection(57%). IgA anti-dengue rapid test can be considered as a new marker for dengue infection, because it gives a high sensitivity, especiallyin the acute phase and in the secondary infections as well.